EU’s recycled content targets of lithium-ion batteries are likely to compromise critical metal circularity - Zhou, Haiwei; Yang, Yuyao; Li, Wen; McKechnie, Jon; Thiede, Sebastian; Wang, Peng (One earth (Cambridge, Mass.), 2024)
Batteries, essential for a net-zero future, are highly dependent on critical metals, the extraction and supply of which inflict harm on society and the environment and are subject to geopolitical tensions. To reduce damages and secure supply, the EU has introduced ambitious targets for end-of-life battery recycling and critical metal recovery; however, the feasibility of such targets remains unclear. Here, to explore the impacts of the EU’s proposed recycled content (RC) targets on battery material circularly, we develop a comprehensive material flow analysis model for the EU’s lithium-ion batteries and consider different climate targets and battery chemistries, lifespans, and repurposing rates. Results show that achieving the EU’s RC targets in 2036, especially for cobalt, is challenging. The RC targets become more achievable via, e.g., maintaining a high rate of manufacturing waste, disincentivizing battery repurposing, and forcing the early retirement of batteries, which could, however, undermine battery material circularity. Our analysis suggests that the EU should remain flexible in its RC targets. [Display omitted] •A comprehensive MFA model was developed for three major lithium-ion battery markets•The EU’s recycled content (RC) targets are analyzed under 108 scenarios•It could be challenging to meet the EU’s RC targets by 2036, especially for cobalt•Meeting the RC targets could compromise other circular economy efforts Batteries are playing an important role in the global transformation of the energy sector, helping to adopt electrification and reduce greenhouse gas emissions. Critical metals, such as cobalt, lithium, and nickel, are essential to battery chemistries and, thus, battery performance. However, mining these metals has led to soil and water contamination, biodiversity degradation, and human rights concerns, while geopolitical tensions are inflaming supply chain risks. To mitigate these challenges, the EU has introduced a new battery regulation: from 2031 onward, lithium-ion batteries that enter the EU marketplace must contain a minimum level of recycled content for the abovementioned three metals. To meet this legally binding target, battery manufacturers need to procure sufficient recycled battery materials. Based on our investigation of the supply-demand flows of these three critical metals under various scenarios, it is challenging to fulfill the EU’s recycled content targets unless counterintuitive actions that compromise sustainability are taken by manufacturers. Our study encourages stakeholders to reexamine the feasibility of RC targets so that they align with circularity aspirations. The EU has proposed new rules for adopting recycled materials in new batteries, aiming to promote battery recycling and enhance battery sustainability. This will force battery manufacturers to procure sufficient recycled battery materials to enter the EU market. However, the feasibility and implications of the EU new rules remain unknown. Here, we fill the knowledge gap by exploring how the EU’s new rules interact with the availability of recycled materials using a comprehensive material flow analysis under 108 scenarios. We reveal the unintended negative impacts of the new rules on battery material circularity, providing valuable insights for future policy-making efforts.